Pd nanoparticles decorated on a porous Co(BDC-NH2) MOF as an effective heterogeneous catalyst for dye reduction - Keypour, Hassan; Kouhdareh, Jamal; Rabiei, Khadijeh; Karakaya, Idris; Karimi-Nami, Rahman; Alavinia, Sedigheh (Royal Soc Chemistry, 2023)
Herein, a new catalytic nanocomposite [Co(BDC-NH2)-Pd NPs] composed of a Co(BDC-NH2) MOF has been developed. The catalyst was prepared by modifying the synthesized porous Co(BDC-NH2) MOF with decorated Pd nanoparticles. This nanocatalyst was used as a heterogeneous catalyst in the reductive degradation of organic dyes Rhodamine B and methyl orange with NaBH4. The kinetic and thermodynamic parameters of the reactions were evaluated. The results showed that the low catalyst content could successfully catalyze the dye reduction reaction quickly (1 min). The metal-organic frameworks unique porous morphology of the Co(BDC-NH2) MOF appears to increase dye adsorption and achieve effective dye reduction. Additionally, recyclability studies of the catalyst confirmed that it could be recovered and reused for 10 consecutive reaction cycles with negligible Pd leaching and reduction in catalytic activity.
Keywords: Au Nanoparticles; Methylene-Blue; Eley-Rideal; Oxidation; Nanocomposites; Hydrogenation; Composite; Graphene